(untitled) (Kairaranga, 2011)
Since 1989, teacher aides have become a familiar part of our classrooms as they support students with special educational needs. International and New Zealand research shows that despite many teacher aide practices that effectively support student learning in inclusive settings, there are some practices that work against the inclusion of some students and therefore, their academic and social learning needs are not being met. As part of a study that examined friendships and social relationships, four secondary school students with severe physical disabilities, teacher aides and teachers shared their stories. These stories complement other research studies and indicate that some schools are not addressing issues relating to the use of teacher aides. This study provides recent narrative data to inform policy and practice in relation to the use of teacher aides in inclusive settings.